A critical review of NanoSIMS in analysis of microbial metabolic activities at single-cell level. (2nd September 2016) - Gao, Dawen; Huang, Xiaoli; Tao, Yu
Abstract: Over 3.8 billion years of evolution has enabled many microbial species a versatile metabolism. However, limited by experimental methods, some unique metabolism remains unknown or unclear. A major obstacle is to attribute the incorporation of certain nutrients into a noncultivable species out of a complex microbial community. Such difficulty could be solved if we are able to directly observe substrate uptake at the single-cell level. Nanoscale secondary ion mass spectrometry (NanoSIMS) is a powerful tool for revealing element distribution in nanometer-scale resolution in the fields such as material sciences, geosciences and astronomy. In this review, we focus on another applicability of NanoSIMS in microbiology. In such fields, physiological properties and metabolic activities of microorganisms can be revealed with a single-cell scale resolution by NanoSIMS solely or in combination with other techniques. This review will highlight the features of NanoSIMS in analyzing the metabolic activities of carbon, nitrogen, metal irons by mixed-culture assemblies. Some values of NanoSIMS in environmental microbiology are expected to be discussed via this review.